2011
DOI: 10.1038/nature10533
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing reveals insights into physiology and longevity of the naked mole rat

Abstract: The naked mole rat (NMR, Heterocephalus glaber) is a strictly subterranean, extraordinarily long-lived eusocial mammal1. Although the size of a mouse, its maximum lifespan exceeds 30 years and makes this animal the longest living rodent. NMRs show negligible senescence, no age-related increase in mortality, and high fecundity until death2. In addition to delayed aging, NMRs are resistant to both spontaneous cancer and experimentally induced tumorigenesis3,4. NMRs pose a challenge to the theories that link agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
540
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 531 publications
(592 citation statements)
references
References 28 publications
25
540
2
3
Order By: Relevance
“…POLB, involved in DNA maintenance, replication, and recombination, was among the top 1% hits at the 0.2 threshold but with a modest score of 3.3. Interestingly, three proteins among our hits were also recently reported to be under positive selection in the long-lived naked mole rat: COL3A1, PRKD2, and GSTO1 (Kim et al 2011). Fig.…”
Section: Detecting Longevity-specific Selection In Proteinsmentioning
confidence: 66%
See 1 more Smart Citation
“…POLB, involved in DNA maintenance, replication, and recombination, was among the top 1% hits at the 0.2 threshold but with a modest score of 3.3. Interestingly, three proteins among our hits were also recently reported to be under positive selection in the long-lived naked mole rat: COL3A1, PRKD2, and GSTO1 (Kim et al 2011). Fig.…”
Section: Detecting Longevity-specific Selection In Proteinsmentioning
confidence: 66%
“…CAPNS1, scoring 4.0 (rank 7; moderate), belongs to a well-conserved family of calcium-dependent, cysteine proteases whose link to cellular senescence and DNA damage response has been studied (Demarchi and Schneider 2007). COL3A1 (rank 4; relaxed) is a collagen-type protein whose expression is downregulated with age across tissues (de Magalhães et al 2009b) and has also been reported to be under positive selection in the long-lived naked mole rat (Kim et al 2011), making it a top candidate for selection in longlived lineages. Also, TAOK3 (rank 7; relaxed) is a serine/threonine-protein kinase whose overexpression may activate ERK1/ERK2 and JNK/SAPK (Zhang et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We obtained a 31-nucleotide depth distribution and observed that the peak depth was at 70. The following formula 48 was applied: genome size = total_kmer_ num/kmer_depth, where total_kmer_num is the total number of K-mers in the sequence, and kmer_depth is the peak depth on the K-mer frequency distribution map. Using this method, the size of the G. hirsutum genome is estimated to be 2.5 Gb.…”
Section: Methodsmentioning
confidence: 99%
“…We used TreeFam 7.0 (http://www.treefam.org/) to define gene families among 15 mammalian genomes: human, chimpanzee, gorilla, orangutan, rhesus macaque, marmoset, Chinese tree shrew, northern tree shrew, rabbit, mouse, rat, dog, cow, opossum and platypus. We carried out the same pipeline and parameters used in our previously published study 58 . We obtained 18,823 gene families and 2,117 single-copy orthologues.…”
Section: Methodsmentioning
confidence: 99%